Glass-ionomer fissure sealants: Clinical observations up to 13 years. (December 2018) - Markovic, Dejan; Peric, Tamara; Petrovic, Bojan
Abstract: Objectives: The aim of this study was to clinically examine the retention and caries-preventive effect of a glass-ionomer material for fissure sealing in newly erupted permanent molars. Methods: A total of 1736 newly erupted permanent molars were sealed in 480 children aged 5–15 years. Sealants were evaluated yearly and recorded as "completely retained", "partially retained", or "completely lost". Teeth were also evaluated for presence of caries. Results: Sealants were observed for 2–13 years. The mean follow-up time was 5 years. After one year, 69% of the sealants were fully retained and 21% were partially retained. Thereafter, the cumulative retention rate decreased. Starting from 8th year of follow-up, no "completely retained" sealant could have been observed. At the end of the 13-year follow-up period, 76% of sealants were "completely lost". On the other hand, 99% and 65% of observed occlusal surfaces were caries-free after one and 13 years, respectively. During the observation period, 62 teeth developed caries in surfaces other than occlusal. Survival rates were significantly better for second permanent molars than for first permanent molars (p < 0.001). No influence of caries risk on caries incidence has been noted. Conclusions: Although the retention rate of the glass-ionomer material for fissure sealing was low, it appears to have prevented dental caries in 65% of newly erupted permanent molars evaluated after thirteen years of placement. Clinical significance: The present study reports long-term clinical performance of glass-ionomer fissure sealants in patients with low, moderate and high caries-risk. The study shows that caries risk does not influence survival of glass-ionomer sealants, which proved to be beneficial for long-term caries protection.